Fémininmasculin le sexe de l'art. - Centre Georges Pompidou; Barré, Francois (Paris : Georges Pompidou, 1995)
Abramovic, Marina & Ulay ; Acconci, Vito ; Alberola, Jean-Michel ; Antoni, Janine ; Arp, Hans (Jean) ; Artaud, Antonin ; Baquié, Richard ; Bellmer, Hans ; Benglis, Lynda ; Blocher, Sylvie ; Blondel, Michèle ; Blossfeldt, Karl ; Boiffard, Jacques-André ; Bourgeois, Louise ; Brancusi, Constantin ; Brauner, Victor ; Bruly-Bouabré, Frédéric ; Byars, James Lee ; Cahun, Claude ; Calle, Sophie ; Chadwick, Helen ; Chauvin, Jean ; Clark, Larry ; Clark, Lygia ; Clemente, Francesco ; de Clérambault, Gaëtan Gatian ; Combas, Robert ; Coplans, John ; Corpet, Vincent ; Courbet, Gustave ; Creten, Johan ; Cunningham, Imogen ; Dali, Salvador ; Dietman, Erik ; Dix, Otto ; Dubuffet, Jean ; Duchamp, Marcel ; Dumas, Marlene ; Dunning, Jeanne ; Ernst, Max ; Export, Valie ; Fabro, Luciano ; Fauguet, Richard ; Fautrier, Jean ; Fischl, Eric ; Flanagan, Barry ; Fleury, Sylvie ; Fontana, Lucio ; Galan, Julio ; Gette, Paul-Armand ; Giacometti, Alberto ; Gilbert & George ; Gober, Robert ; Goldin, Nan ; Gotscho ; Grosz, George ; Guilleminot, Marie-Ange ; Hatoum, Mona ; Hausmann, Raoul ; Hesse, Eva ; Hirakawa, Noritoshi ; Holzer, Jenny ; Horn, Rebecca ; Hyber, Fabrice ; Johns, Jasper ; Jones, Allen ; Journiac, Michel ; Kahlo, Frida ; Kapoor, Anish ; Kelley, Mike ; Klauke, Jürgen ; Klee, Paul ; Klein, Yves ; Klossowski, Pierre ; de Kooning, Willem ; Krystufek, Elke ; Kudo, Tetsumi ; Lachaise, Gaston ; Lambert, Alix ; Lassnig, Maria ; Lebel, Jean-Jacques ; Leonard, Zoe ; Leroy, Eugène ; Lublin, Léa ; Lucas, Sarah ; Magritte, René ; Mallo, Maruja ; Man Ray ; Mapplethorpe, Robert ; Martin, Etienne ; Masson, Andre ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; McCarthy, Paul ; Mendieta, Ana ; Merz, Mario ; Messager, Annette ; Miro, Joan ; Modotti, Tina ; Molinier, Pierre ; etc.
Fémininmasculin: le sexe de l'art, Centre Pompidou, Paris, 24.10.1995 - 12.02.1996
kunstcatalogus